A Longitudinal Analysis of the Trajectories and Predictors of Word Reading and Reading Comprehension Development Among At-Risk Readers. (May 2019) - Peng, Peng; Fuchs, Douglas; Fuchs, Lynn S.; Elleman, Amy M.; Kearns, Devin M.; Gilbert, Jennifer K.; Compton, Donald L.; Cho, Eunsoo; Patton, Samuel
This study explored the developmental trajectories and predictors of word reading and reading comprehension among young at-risk readers. In fall of first grade, 185 students identified as at-risk for reading difficulties were assessed on measures of domain-specific skills (phonological awareness, letter knowledge, and vocabulary), domain-general skills (working memory, nonverbal reasoning, and processing speed), and word reading and reading comprehension. Word reading and reading comprehension were assessed again in spring of grades 1–4. Individual growth curve modeling showed that the children demonstrated decelerated growth on word reading and linear growth on reading comprehension, although their performance on both word reading and reading comprehension were consistently below average on national norms. After controlling for word reading and reading comprehension in first grade, letter knowledge predicted growth in word reading; vocabulary and nonverbal reasoning predicted growth in reading comprehension. That is, we found different developmental trajectories and different predictors for word reading and reading comprehension among our at-risk sample. Implications are discussed for theory and early reading instruction for at-risk children.